2020
DOI: 10.1186/s12881-020-0965-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the polymorphisms of site RS4977574, and RS1333045 in region 9p21 and the susceptibility of coronary heart disease in Chinese population

Abstract: Background: Rs4977574 (A > G) and Rs1333045 (C > T) are both single nucleotide polymorphisms (SNPs) related with coronary artery disease, locating on chromosome 9p21.3. The study aimed to identify the correlation between rs4977574 and rs1333045 polymorphism genotypes and coronary heart disease (CHD) in a Chinese population. Methods: Blood samples were collected from 855 subjects. A case-control study was used in this experiment, and 598 cases in the CHD group and 257 subjects in the control group were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The information was drawn out from 18,430 CHD cases and 22,549 controls (Table 1 ). 9 , 10 , 11 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 Of the 35 obtained literatures after the preliminary search course, 17 met the present meta‐analysis including criteria. Among the eighteen eliminated papers, five of them were of review character.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The information was drawn out from 18,430 CHD cases and 22,549 controls (Table 1 ). 9 , 10 , 11 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 Of the 35 obtained literatures after the preliminary search course, 17 met the present meta‐analysis including criteria. Among the eighteen eliminated papers, five of them were of review character.…”
Section: Resultsmentioning
confidence: 99%
“… 9 Analogously, in 2020, Hua et al examined the association between CDKN2B ‐ AS1 gene rs4977574 polymorphism and CHD in a Chinese population and found that the G allele is the CHD susceptibility site. 10 On the contrary, in 2007, Samani et al 11 reported that the G allele frequency was greatly lower in CHD patients than that in controls in a WTCCC study of a British population.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…After the screening, 4,131 articles were excluded by their title and abstract. Next, 55 articles were further estimated by their contents, of which 5 articles provided lipid data by the genotypes of rs1333049 ( 39 , 40 ), rs4977574 ( 41 ), rs10757274 ( 42 ), and rs10811661 ( 43 ) but expressed as a median and interquartile range (IQR), 3 articles provided lipid data by the genotypes of rs1333049 but human subjects used lipid-lowering drugs ( 44 46 ), 2 articles provided the percentage change of lipid data by the genotypes of rs1333049 ( 47 , 48 ), 1 article did not present genotype counts of rs1333049 ( 17 ), and 1 article ( 49 ) provided lipid levels by the genotypes of rs1333049 but in an aberrant genetic model [(CG + GG) vs. CC]. Therefore, 12 articles were further excluded.…”
Section: Resultsmentioning
confidence: 99%
“…The up-regulation of hs-CRP mainly affects the spasm of coronary artery vessels and the deposition of subendothelial adipose tissue. In turn, it affects the stenosis of vascular lumen, leading to cardiomyocyte ischemia and the occurrence of CHD [19][20][21][22] . In the process of increasing the number of coronary artery lesions, the expression of hs-CRP also increased significantly, suggesting that there may be a potential relationship between the expression of hs-CRP and the number of coronary artery lesions, mainly because the change of the expression concentration of hs-CRP can increase the risk of low density lipoprotein and triglyceride deposition, resulting in an increase in the risk of coronary artery branch occlusion in patients [23][24][25] .…”
Section: Resultsmentioning
confidence: 99%